Distribution of a Newly Recorded Gastropod Species, Mainwaringia leithii (Gastropoda, Littorinidae), in Young, Rehabilitated Mangroves in China - Chen, Shunyang; Xing, Bingpeng; Yu, Weiwei; Chen, Bin; Liao, Jianji; An, Wenshuo; Chen, Guangcheng (Frontiers in Marine Science, 2021)
The species within the genus Mainwaringia in Littorininae have been recognized as being strongly associated with mangroves; however, their abundance and distribution patterns in mangroves have rarely been reported. In this study, we reported Mainwaringia leithii specimens collected from young, rehabilitated mangroves in Xiamen city as a newly recorded Mainwaringia species in China, based on their DNA barcoding and morphological taxonomy characteristics. The recruitment pattern of this species and its relationships with mangrove species in the early stage of mangrove rehabilitation were also investigated. The snails were mainly collected from the backsides of leaves and from some leaf nodes. Continuous sampling showed the rapid recruitment of M. leithii following mangrove rehabilitation, with a density up to 278 ind m-2 in a 2.5-year-old mangrove site; however, declining densities were observed and snails were only occasionally collected at mangrove sites 4 years after rehabilitation. Aegiceras corniculatum mangroves in shrub form could support an snail abundance higher than that supported by Kandelia obovata mangroves of the same age. The present study suggests that M. leithii could be common in mangrove forests and that intensive changes in its assemblage occur in the early stage of mangrove rehabilitation. Moreover, the recruitment of M. leithii following mangrove rehabilitation is related to the planting of different mangrove species. The spatio-temporal patterns of M. leithii distribution are likely owing to the variability in habitat characteristics related to mangrove species and stand age. Future studies should give more attention to the ecology of this species in mangrove forests.